The husbands - Baker, Chandler (Sydney, NSW : Hachette Australia, 2021)
"Welcome to the neighbourhood. We do things differently here. Recently, Nora has started to feel that 'having it all' - a family, a soon-to-be new house, a successful career in law - comes with a price, one her husband, Hayden, doesn't seem to be paying quite so heavily. Then her house-hunting takes them to an affluent suburban neighbourhood and Nora's eyes are opened to a new world. One where women can have it all. One where the men actually pull their weight. But as a wrongful death case involving one of the local residents draws Nora further into this perfect world, she begins to realise that the secret of 'having it all' is far more complicated than she could ever have imagined. In fact, it may be worth killing for... " -- Back cover.
"How far would you go for a little more help from your husband?" -- Front cover.
Keywords: Neighborhoods -- Fiction; Husband and wife -- Fiction; Wrongful death -- Fiction; Secrecy -- Fiction; Feminists -- Fiction; Modern & contemporary fiction; Australian